Sertraline-induced hypersensitivity pneumonitis. Issue 12 (19th December 2019) - Virdee, Gursharan; Bleasdale, John; Ikramullah, Mohammed; Graham-Clarke, Emma
Abstract : Hypersensitivity pneumonitis (HP), also known as extrinsic allergic alveolitis, is a granulomatous, non-IgE-mediated hypersensitivity reaction of the alveoli and distal bronchioles presenting as an acute, subacute or chronic condition. It is most commonly associated with exposure to extrinsic allergens (eg, avian dust, mould and tobacco) and medications including antiarrhythmics (eg, amiodarone), cytotoxics (eg, methotrexate) and antiepileptics (eg, carbamazepine). Individuals diagnosed with this condition can present with severe hypoxia and respiratory failure. The fundamental principle of management is to remove the causative allergen. Evidence implicating selective serotonin reuptake inhibitors as a causative agent is limited, and this case report describes a rare clinical presentation of HP associated with sertraline, how it was diagnosed and subsequently treated. It is anticipated that raising awareness of this interaction will assist multidisciplinary teams, managing patients diagnosed with HP, to be more cognisant of sertraline as being an aetiological factor for this condition.